Electrostatics and Electrochemistry: Mechanism and Scope of Charge-Transfer Reactions on the Surface of Tribocharged Insulators - Zhang, J.; Coote, M.L.; Ciampi, Simone (AMER CHEMICAL SOC, 2021)
The phenomenon of surface electrification upon contact is a long-standing scientific puzzle, with for instance written accounts of charged samples of amber attracting feathers dating back to the 600 B.C. Electrostatic hazards associated with electrical insulators subject to mechanical friction are well documented, and the design of commercial products, such as copiers and laser printers, is based on the static charging of electrical insulators. Nonetheless, the physical-chemical origin of this phenomenon remains debated. This Perspective outlines recent advances in our understanding of the mechanism behind contact electrification, as well as the emerging research area of electrochemistry on insulators. Research is beginning to demonstrate how to exploit static charges present on insulating surfaces, with the goal of driving redox reactivity. These studies have helped to clarify the triboelectrification mechanism and have defined new platforms for electrochemiluminescence, metal nucleation, and mask-free lithography. This Perspective will help researchers working within electrochemistry, physics, green energy, sensing, and materials to gain an understanding of the implications of contact electrification to their respective fields. Special attention is given to the chemical, electronic, and mechanical factors influencing triboelectrochemical reactions, concluding with the perceived challenges facing further development of this field.